2000
DOI: 10.1016/s1074-7613(00)80221-6
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cells Permit Identification of Genes Encoding MHC Class II–Restricted Epitopes of Transplantation Antigens

Abstract: Minor or histocompatibility (H) antigens are recognized by CD4+ and CD8+ T lymphocytes as short polymorphic peptides associated with MHC molecules. They are the targets of graft versus host and graft versus leukemia responses following bone marrow transplantation between HLA-identical siblings. Several genes encoding class I-restricted minor H epitopes have been identified, but approaches used for these have proved difficult to adapt for cloning class II-restricted minor H genes. We have combined the unique an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
90
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(91 citation statements)
references
References 70 publications
1
90
0
Order By: Relevance
“…Stimulator cells were pulsed with 1000 ng/mL K k -restricted (TENSGKDI) HY peptide 20 (encoded by the Smcy gene) or with the D b -restricted Smcy (KCSRNRQYL), 23 the Uty (WMHHNMDLI) 24 encoded, and the A brestricted Dby encoded (NAGFNSNRANSSRSS) 25 HY peptides at 37°C for 2 hours. Unpulsed irradiated CBA or C57BL/6 female splenocytes were used as negative controls.…”
Section: Antigenic Peptidesmentioning
confidence: 99%
“…Stimulator cells were pulsed with 1000 ng/mL K k -restricted (TENSGKDI) HY peptide 20 (encoded by the Smcy gene) or with the D b -restricted Smcy (KCSRNRQYL), 23 the Uty (WMHHNMDLI) 24 encoded, and the A brestricted Dby encoded (NAGFNSNRANSSRSS) 25 HY peptides at 37°C for 2 hours. Unpulsed irradiated CBA or C57BL/6 female splenocytes were used as negative controls.…”
Section: Antigenic Peptidesmentioning
confidence: 99%
“…One experiment of this type, conducted in von Boehmer's laboratory, asked what would happen if most T cells express a transgenic, class I restricted TCR specific for the antigen H-Y and then meet their target antigen, more or less ubiquitously expressed on tissues of male (but not female) mice [5]. Since these experiments were reported, the H-Y antigen has been characterized as several male cell derived peptides, bound to class I and II molecules, and originating from the sequences of a number of Y chromosome encoded genes that have differential sequence from the X chromosome copy [6]. The initial studies showed that most of the autoreactive, TCR transgenic T cells engaged H-Y peptides in the thymus and were deleted at the CD4 + CD8 + double positive stage of differentiation [5].…”
Section: Transgenic Mice For the Analysis Of Mechanisms Of Central Anmentioning
confidence: 99%
“…Currently, these hypotheses cannot be resolved because the identities of the H Ags recognized by the anti-21M CTL or the anti-H46 CD4 Th cells are unknown. However, they are now accessible by the strategies described here and those recently described by Simpson and her colleagues (13).…”
Section: Discussionmentioning
confidence: 93%
“…Only 10 unique antigenic precursors are known in mice, where H loci have been extensively studied by genetic, biochemical, and immunological methods and have served as models for the study of graft rejection and the immune system itself. Two of these (ND1, COI) are encoded by the mitochondrial (8,10), another three (Smcy, Uty, and Dby) by the Y (11)(12)(13), and four others by autosomal chromosomes (14 -17). For each of these H loci, the donor and host differ in transcriptional regulation or in polymorphic amino acid substitutions within the antigenic peptides, explaining why host CD8 T cell responses were induced to donor peptide-MHC complexes (11,12,16).…”
mentioning
confidence: 99%